2022
DOI: 10.1002/jdd.13138
|View full text |Cite
|
Sign up to set email alerts
|

In‐person and virtual assessment of oral radiology skills and competences by the Objective Structured Clinical Examination

Abstract: Purpose Clinical education is an essential part of the Dental School curriculum and assessment is a fundamental component of the teaching‐learning process. Objectives With the purpose of implementing a structured and objective assessment method in the teaching of Oral Radiology, undergraduate dentistry students were submitted to an assessment of clinical competences and skills in radiology by the Objective Structured Clinical Examination (OSCE), applied both in‐person and virtually (VOSCE). Methods The same gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The COVID-19 pandemic has brought about new challenges in dental education, and the need for an online evaluation platform has been recognized [ 10 ]. It is important to note that online evaluation platforms can be designed in many different ways, and their reliability depend on various factors, such as the number of items, types of questions, and methods used to prevent cheating [ 11 ]. Additionally, the reliability of self-reported dental visits may not be as valid as direct clinical examinations, which are considered the gold standard for assessing dental health [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has brought about new challenges in dental education, and the need for an online evaluation platform has been recognized [ 10 ]. It is important to note that online evaluation platforms can be designed in many different ways, and their reliability depend on various factors, such as the number of items, types of questions, and methods used to prevent cheating [ 11 ]. Additionally, the reliability of self-reported dental visits may not be as valid as direct clinical examinations, which are considered the gold standard for assessing dental health [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies have assessed the reliability of virtual OSCEs by calculating Cronbach’s alphas (Oliven et al, 2011 , 2021 ; Porto et al, 2023 ). Porto et al ( 2023 ) conducted virtual OSCE to assess oral radiology skills and competencies of undergraduate dentistry students, and its reliability was compared to that of in-person OSCE for the same participants. The Cronbach’s alphas of virtual OSCE was 0.81, while that of in-person OSCE was 0.61, showing substantial reliability.…”
Section: Discussionmentioning
confidence: 99%
“…These virtual OSCEs are satisfactory, feasible, and cost-effective as per survey results (Langenau et al, 2014;Shaban et al, 2021;Shaiba et al, 2021), questionnaire feedbacks (Skrzypek et al, 2022;Motkur et al, 2022;Garofalo et al, 2023), empirical analysis (Felthun et al, 2021b;Minty et al, 2022), and descriptive qualitative studies (Shorbagi et al, 2022;Saad et al, 2022;Thampy et al, 2022;). Although three studies assessed the reliability of virtual OSCEs by calculating Cronbach's alphas, and they were about 0.80 (Oliven et al, 2011(Oliven et al, , 2021Porto et al, 2023), a reliability analysis based on G-theory is yet to be reported (Kunutsor et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The exam is conducted using defined methods and assessment tools to assure the validity and reliability of the remote OSCE. The utilization of digital tools like high-resolution cameras and real-time video conferencing software also contributes to a more realistic and immersive experience for both students and standardized patients (32)(33)(34).…”
Section: Virtual Oscementioning
confidence: 99%